Prevalence of malnourishment and predictive factors associated with the nutritional status of gynecologic cancer patients undergoing chemotherapy: a cross-sectional analysis - Khemmanat Sanguanwongthong; Prapaporn Suprasert (Korean Society of Obstetrics and Gynecology, 2022)
Objective To investigate the prevalence and predictive factors of malnourishment in patients with gynecologic cancer during chemotherapy. Methods A total of 101 patients treated with chemotherapy between April 2020 and February 2021 were interviewed using the patient-generated subjective global assessment (PG-SGA). Clinical and laboratory data were also collected. The total number of lymphocytes per cubic milliliter (total lymphocyte count, TLC) and serum albumin were calculated to provide an optimal cut-off point using receiver operating characteristic curves. Clinicopathological variables were compared using univariate and multivariate analyses to identify the independent predictive factors for malnourishment. Results The prevalence of good, moderate, and severe nourishment was 73.3%, 18.8%, and 7.9%, respectively. The optimal cut-off points for TLC and albumin were 1,450 cells/μL and for albumin was 3.9 g/dL. Univariate analysis indicated that the number of chemotherapy cycles ≤3, albumin level ≤3.95 g/dL, body mass index ≤25 kg/m2, TLC <1,450 cells/μL, anemia, and no neutropenia were significantly associated with malnutrition. However, only a serum albumin level ≤3.95 g/dL was independently associated with malnourishment. Conclusion Patients with gynecologic cancer treated with chemotherapy were occasionally found to be malnourished, with the independent predictive predictor being a blood albumin level less than or equal to 3.95 g/dL.